The psychological impact of breast and ovarian cancer preventive options in BRCA1 and BRCA2 mutation carriers. (5th November 2013) - Borreani, C; Manoukian, S; Bianchi, E; Brunelli, C; Peissel, B; Caruso, A; Morasso, G; Pierotti, MA
<x xml:space="preserve">Abstract</x> This study was performed to describe the impact of preventive options on the psychological condition of BRCA1/BRCA2 carriers. A sample of 52 cancer‐affected (C‐A) and 27 cancer‐unaffected (C‐UN) women were enrolled after gene test disclosure (T0). Psychological evaluations were performed at T0 and 15 months later (T1). The surgical options were more likely to be chosen in C‐A women (62%), although a consistent proportion of C‐UN women (30%) also opt for these preventive measures. At the baseline, both samples had average anxiety and depression scores below the cut‐off value, restrained average cancer worry scores and a risk perception consistent with the risk percentage provided during genetic counselling. The longitudinal results indicated no clinically meaningful variations in the anxiety and depression scores in either of the two samples. Statistically significant reductions in cancer‐risk perception emerged in women who chose surgery in both C‐A and C‐UN women. In BRCA1/BRCA2 mutation carriers, surveillance does not influence their initial psychological condition, whereas prophylactic surgery has a significant impact in reducing the perceived risk and worry about getting sick. C‐A and C‐UN women have to be considered as two separate populations of BRCA mutation carriers requiring personalized approaches to risk management.